Drilling Efficiency Analysis Using Drilling Specific Energy Approach: A Comparative Study of Wells RM-01 and RM-02 - Ghani, Muhammad Hafiyyan; Setiati, Rini; Sutresno, Wahyu; Caesar, Athifa Putri (Journal of Earth Energy Science, Engineering, and Technology, 2025)
Drilling operations represent the largest cost component in geothermal field development, particularly when penetrating abrasive volcanic formations that often reduce drilling efficiency and Rate of Penetration (ROP). In the RM geothermal field, the 12¼-inch hole section encounters hard volcanic rocks that pose operational challenges. This study aims to evaluate drilling efficiency and compare performance between wells RM-01 and RM-02 using the Drilling Specific Energy (DSE) approach. A quantitative comparative method was applied using historical drilling data from RM-01 and real-time drilling parameter data from RM-02, including Weight on Bit (WOB), Rotary Speed (RPM), Torque, and Rate of Penetration (ROP). DSE values were calculated using Teale’s specific energy equation and analyzed to identify inefficient drilling zones and evaluate the impact of hydraulic optimization. The results indicate that efficient drilling conditions were achieved only at shallower depths (1200 m in RM-01 and 1500 m in RM-02), where DSE values were relatively low. Hydraulic optimization reduced the average DSE by approximately 43 psi (0.18%) in RM-01 and 510 psi (1.01%) in RM-02, indicating improved drilling efficiency. However, DSE values at deeper intervals remained high, suggesting that formation strength and abrasiveness significantly affect drilling performance. The study is limited by the use of a limited number of wells and the focus primarily on hydraulic optimization without extensive analysis of other mechanical parameters such as bit design, vibration control, and broader lithological variability. Further research incorporating additional wells and integrated mechanical-hydraulic optimization is recommended to achieve more substantial improvements in drilling efficiency.